The Role of Seaweed Cultivation in Improving Community Economy from the Perspective of Islamic Economics in Bone Regency - Muhammad Ilham; Syahriyah Semaun; An Ras Try Astuti; Sitti Jamilah Amin; Mus Mulyadi (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study explores the role of seaweed cultivation in enhancing community economic welfare from a Sharia Economics perspective in Bone Regency, Indonesia. The research aims to analyze the contribution of seaweed farming to economic growth, its impact on production patterns and income distribution, and its alignment with Sharia economic principles. A qualitative case study approach was employed, involving field research through interviews with village officials and community members, supported by secondary data from journals, books, and relevant articles. The findings indicate that seaweed cultivation provides a stable source of income, supports poverty reduction, and encourages ethical and sustainable practices in accordance with Sharia principles. However, challenges such as price fluctuations, climate variability, and limited access to capital remain significant. The benefits of cultivation are unevenly distributed, with larger producers gaining more advantages, highlighting the need for policies that empower small-scale cultivators. From a Sharia perspective, seaweed farming emphasizes justice, balance, sustainability, and ethical entrepreneurship, requiring supportive conditions such as access to capital, training, fair markets, and information. Sustainable production, stable pricing, capacity building, and product diversification are essential to optimize economic and social outcomes. This study contributes to the literature on Sharia-compliant economic development by demonstrating how community-based agricultural practices can generate equitable growth, enhance livelihoods, and foster responsible economic behavior aligned with religious and ethical values.